Esterified Illipe Butter-Based Fatty Amine as a Bio-Based Multifunctional Additive for NR/BR Blends Reinforced with a Silica/Silane System in Green Tire Tread Development - Fathurrohman, Mohamad Irfan; Puspitasari, Santi; Kinasih, Norma Arisanti; Arti, Dewi Kusuma (Journal of Applied Agricultural Science and Technology, 2025)
The sustainable rubber industry, particularly in the tire sector, is supported by the use of biomaterials such as multifunctional additives. Fatty amine, derived from the esterification of illipe butter, is considered a promising bio-based multifunctional additive for the development of green tires. This research aimed to investigate the effect of varying dosage of fatty amine on the properties of green tire treads based on NR/BR blends reinforced with a silica/silane system. DPG and unmodified illipe butter were used as comparative references. The "magic triangle of tire performance" was employed as a benchmark for evaluating green tire tread performance. The result indicated that both unmodified illipe butter and fatty amine functioned as bio based multifunctional additives, specifically serving as a bio-plasticizer (filler dispersant) and fast-delayed bio-accelerator, respectively. Therefore, they have the potential to substitute DPG in rubber formulations. The combination of unmodified illipe butter and fatty amine at dosages of 2.5 and 1.25 phr, respectively, exhibited similar behavior by enhancing rubber-filler interaction. Consequently, they meet the desirable criteria outlined in the magic triangle of tire performance.